# exercises_9 - 3 x 2 3 x 2-3(b lim x → 1 x 2-2 x 1 x 3-x(c...

This preview shows pages 1–2. Sign up to view the full content.

Analysis 1: Exercises 9 1. (a) Prove that lim x a f ( x ) = lim h 0 f ( a + h ) . (b) Prove that lim x a f ( x ) = b if and only if lim x a ± f ( x ) - b ² = 0. 2. Prove the following two theorems. Theorem 1. Let lim x a f ( x ) = A and lim x a g ( x ) = B . Then (i) lim x a ( f ( x ) + g ( x ) ) = A + B ; (ii) lim x a ( f ( x ) · g ( x ) ) = A · B . If in addition B 6 = 0 , then (iii) lim x a ³ f ( x ) g ( x ) ´ = A B . Theorem 2. Let lim x a f ( x ) = A and lim x a g ( x ) = B . Suppose that [( δ > 0) h { x R | 0 < | x - a | < δ } ⊆ D ( f ) D ( g ) i and ( 0 < | x - a | < δ ) ± f ( x ) g ( x ) ² . Then A B ; that is, lim x a f ( x ) lim x a g ( x ) . 3. Let lim x 0 f ( x ) = 0. Prove that (a) lim x 0 f (2 x ) = 0; (b) lim x 0 f ( x 2 ) = 0. 4. Compute the following limits: (a) lim x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 3 x 2 + 3 x 2-3 ; (b) lim x → 1 x 2-2 x + 1 x 3-x ; (c) lim x → 1 x-1 √ x-1 . 5. We deﬁne lim x → a f ( x ) = + ∞ to mean that ( ∀ M ∈ R )( ∃ δ > 0)( ∀ x ∈ D ( f )) h ( < | x-a | < δ ) ⇒ ( f ( x ) > M ) i . (a) Prove that lim x → 3 1 ( x-3) 2 = + ∞ . 2 (b) Deﬁne lim x → a + f ( x ) = + ∞ and prove that lim x → 0+ 1 x = + ∞ ....
View Full Document

## This note was uploaded on 02/25/2010 for the course MATHEMATIC 11007 taught by Professor Spyros during the Winter '10 term at Bristol Community College.

### Page1 / 2

exercises_9 - 3 x 2 3 x 2-3(b lim x → 1 x 2-2 x 1 x 3-x(c...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online